CUMPLIMIENTO DE LAS PRESTACIONES A EMPLEADOS DE EMPRESAS DE OUTSOURCING EN MÉXICO - López, Rafael Díaz; Tecillo, Francisco Javier Jimenez; Magaña, Sergio Alfonso Tosca (IJRDO - Journal of Business Management, 2021)
Outsourcing has caused a lot of controversy since there is so much confusion both from the employer's area and those who are hired by outsourcing companies, although the authorities over the years have tried to regulate and delimit this type of hiring, there are still many loopholes where the rights of workers are unprotected and even tax evasion by companies. It is believed that more than 50% of the workers that are related to Outsourcing labor contracts do not know or ignore what it entails to accept this type of labor contract, since in some cases their labor rights may be violated and since they do not know about the subject, they cannot defend themselves before their employers.